Review articleMetabolic syndrome in the year 2006 - Kocięcki, Marek (Przegląd Kardiodiabetologiczny/Cardio-Diabetological Review, 2006)
The article presents the history, present definitions and criteria of metabolic syndrome and its role in development of cardiovascular diseases and type 2 diabetes. It also mentions controversies surrounding the criteria and the role of the syndrome. The metabolic syndrome has become more common in the world. People with the metabolic syndrome are at increased risk of cardiovascular diseases and type 2 diabetes. The metabolic syndrome is characterized by a group of metabolic risk factors, such as abdominal obesity, atherogenic dyslipidaemia, elevated blood pressure and insulin resistance or glucose intolerance. The dominant underlying risk factors for this syndrome come into view to be abdominal obesity and insulin resistance. Other conditions linked with the syndrome include physical inactivity, age, hormonal disorder and genetic predisposition. The main goal of clinical management of the metabolic syndrome is to reduce the risk for diseases related to plaque buildups in artery walls, especially coronary heart disease, stroke, peripheral vascular disease and type 2 diabetes.